The Role Extracorporeal Membrane Oxygenation in Acute Respiratory Distress Syndrome - Widhy Yudistira Nalapraya; Menaldi Rasmin; Zuswayudha Sjamsu (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Treatment of oxygen therapy should be based on appropriate indication and dose of administration. British Thoracic Society (BTS) recommends oxygen therapy were administered with a 94–98% saturation target in most acute patients and for patients with hypercapnic respiratory failure, BTS recommends 88-92 saturation target or spesific saturation target. Acute respiratory distress syndrome (ARDS) is characterized by acute, diffuse, inflammatory lung injury leading to increased capillary permeability in the alveolus with clinical manifestations of hypoxemia and bilateral opafication. The use of extracorporeal membrane oxygenation (ECMO) along with mechanical ventilator can be useful for ARDS patients and can improve survival.